2021
DOI: 10.1186/s12951-021-01123-9
|View full text |Cite
|
Sign up to set email alerts
|

Engineered extracellular vesicles derived from primary M2 macrophages with anti-inflammatory and neuroprotective properties for the treatment of spinal cord injury

Abstract: Background Uncontrollable inflammation and nerve cell apoptosis are the most destructive pathological response after spinal cord injury (SCI). So, inflammation suppression combined with neuroprotection is one of the most promising strategies to treat SCI. Engineered extracellular vesicles with anti-inflammatory and neuroprotective properties are promising candidates for implementing these strategies for the treatment of SCI. Results By combining ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 46 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…100 NGF bound to macrophage vesicles via MMP9 and is precisely released at the site of injury. In vitro experiments confirmed that EVs-cl-NGF had no toxic effect on neural cells (Figure 4 55 target the inflammatory site in mice within 2 h, peaking at 12 h. In vitro experiments confirmed that Cur@EVs induced a considerable reduction in the expression of proinflammatory factors-that was, TNF-α, IL-1β, and IL-6and an increase in the expression of anti-inflammatory factors (TGF-β), the proportion of M1 macrophage subsets decreasing to 26.90%, and the proportion of the M2 macrophage subset increasing to 31.77% (Figure 4(d)).…”
Section: Gels/scaffolds That Deliver Signaling Moleculesmentioning
confidence: 74%
“…100 NGF bound to macrophage vesicles via MMP9 and is precisely released at the site of injury. In vitro experiments confirmed that EVs-cl-NGF had no toxic effect on neural cells (Figure 4 55 target the inflammatory site in mice within 2 h, peaking at 12 h. In vitro experiments confirmed that Cur@EVs induced a considerable reduction in the expression of proinflammatory factors-that was, TNF-α, IL-1β, and IL-6and an increase in the expression of anti-inflammatory factors (TGF-β), the proportion of M1 macrophage subsets decreasing to 26.90%, and the proportion of the M2 macrophage subset increasing to 31.77% (Figure 4(d)).…”
Section: Gels/scaffolds That Deliver Signaling Moleculesmentioning
confidence: 74%
“…Recently, a new method that improves bioavailability by combining curcumin with extracellular vesicles was reported. 55 In the study, 120-nm engineered extracellular vesicles derived from primary M2 macrophages were used and nerve growth factors and curcumin were combined. The extracellular vesicles could effectively accumulate curcumin at the site of SCIs and inhibit uncontrollable inflammatory responses induced by secondary injury.…”
Section: Obstacles and Future Directionmentioning
confidence: 99%
“…PA–C also enhanced neuroprotection, axonal development, and functional recovery in acute SCIs. Recently, a new method that improves bioavailability by combining curcumin with extracellular vesicles was reported [ 55 ]. In the study, 120-nm engineered extracellular vesicles derived from primary M2 macrophages were used and nerve growth factors and curcumin were combined.…”
Section: Obstacles and Future Directionmentioning
confidence: 99%
“…Exosomes with good biocompatibility are likely to play an important role in the clinical application of SCI [ 6 , 7 ]. Exosomes can effectively promote functional recovery after SCI through their immunomodulatory, anti-inflammatory [ 8 , 9 ], and antiapoptotic effects as well as their role in promoting vascular and axon regeneration [ 10 , 11 ]. However, the specific mechanism is not clear and remains to be explored.…”
Section: Introductionmentioning
confidence: 99%